Regulation of Cardiac Excitability Protein Kinase C Isozymes - Ferreira, Julio Cesar Batista (2012)
Cardiac excitability and electrical activity are determined by the sum of individual ion channels, gap junctions and exchanger activities. Electrophysiological remodeling during heart disease involves changes in membrane properties of cardiomyocytes and is related to higher prevalence of arrhythmia-associated morbidity and mortality. Pharmacological and genetic manipulation of cardiac cells as well as animal models of cardiovascular diseases are used to identity changes in electrophysiological properties and the molecular mechanisms associated with the disease. Protein kinase C (PKC) and several other kinases play a pivotal role in cardiac electrophysiological remodeling. Therefore, identifying specific therapies that regulate these kinases is the main focus of current research. PKC, a family of serine/threonine kinases, has been implicated as potential signaling nodes associated with biochemical and biophysical stress in cardiovascular diseases. Thus, the role of PKC isozymes in regulating cardiac excitability has been a subject of great attention. In this review, we describe the role of PKC isozymes that are involved in cardiac excitability and discuss both genetic and pharmacological tools that were used, their attributes and limitations. Selective and effective pharmacological interventions to normalize cardiac electrical activities and correct cardiac arrhythmias will be of great clinical benefit.